Developing performance instruments assessment of 5th grade elementary school students in integrated thematic learning - Ifan Awanda; Alben Ambarita; Rochmiyati Rochmiyati; Dwi Yulianti (Lighthouse Publishing, 2021)
This study aims to develop an instrument for assessing student performance in elementary schools. The type of research and development used refers to the R&D theory of Borg and Gall. This study was conducted in three schools in Bandar Lampung. The sample data of this research were taken from the fifth-grade students of SD Negeri 1 Perumnas Way Halim. For data collection, observation, questionnaires, and documentation were employed, with descriptive analysis of the percentage of expert and practitioner validation, followed by instrument analysis for validity and reliability. This finding indicates that the assessment performance instruments of students in elementary schools were developed with theoretical and practical feasibility. Suggestions and limitations for future research are also discussed.